Resilience Strategies for Mismatched Workers: Microeconomic Evidence from Egypt - Hélène Syed Zwick (Global Labor Organization (GLO), 2020)
Purpose – The purpose of this paper is to identify and discuss the on-the-job resilience strategies of mismatched workers. We empirically focus on Egyptian workers.Design/Methodology/Approach – This study relies on a primary micro-data collection based on design and implementation of a self-administered questionnaire survey and on the conduction of a series of semi-structured interviews. Findings – The results are fourfold: first, the combination of over-qualification and under-skilling is the most frequent in our sample; second, resilience strategies adopted by over-skilled workers mainly depend on mobility and entry to entrepreneurship; third, under-skilled workers do not enter entrepreneurship, but tend to rely on informal on-the-job learning and training opportunities. Fourth, religion and spirituality play a transversal role to cope with adversity for all of our interviewed workers. Originality/value – This study is unique as it draws our attention on factors of resilience for mismatched workers in a developing country, Egypt.
Keywords: J24; E24; C81; 330; resilience strategies; skill mismatches; qualification mismatches; Egypt